Pendampingan Penyusunan Indeks Kelayakan Investasi Desa di Kota Batu - Idah Zuhroh; Muhammad Sri Wahyudi Suliswanto; Hendra Kusuma; Fitri Rusdianasari (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2025)
The community service conducted a study on data management in Bulukerto, Tlekung, and Gunungsari Villages in Batu City. Local potential, especially in the agricultural sector, has not been optimally utilized due to fragmented and unintegrated data systems. The main problems include the lack of data by name by address, limited access to digital services, and weak documentation of superior potential such as apples, oranges, and cut flowers. The method used involves the development of a digital-based data integration system, with stages of identifying data needs, collecting and processing data, and training village officials. This program also includes statistical training and coaching to improve the capacity of village officials in analyzing and presenting data. The results show significant improvements in village data management. The integration system allows the preparation of a Village Investment Feasibility Index that includes dimensions of business finance, economy, investment climate, and infrastructure. This index is based on indicators such as financial literacy, access to digital services, and local consumption potential. The benefits achieved include strengthening the capacity of village officials, providing comprehensive individual-based data, and more strategic village development planning. This feasibility index is expected to be an effective guide for villages in attracting investment based on local potential and improving community welfare.